Chemotherapy related encephalopathy in a patient with Stage IV cervical carcinoma treated with cisplatin and 5-fluorouracil: a case report - Chue, Amy L (Cases Network Ltd, 2009)
INTRODUCTION: Chemotherapy related encephalopathy is commonly reported with certain forms of chemotherapy but few reports note an association with low dose 5-Fluorouracil. CASE PRESENTATION: A 57-year-old Caucasian lady received her first cycle of Cisplatin and 5-Fluorouracil for palliative treatment of cervical carcinoma, and presented several days later with signs of encephalopathy. Several causes were eliminated, and encephalopathy related to 5-Fluorouracil was thought to be the most likely cause. Magnetic Resonance Imaging of the head revealed changes related to the chemotherapy received. Symptoms resolved completely within three days of presentation. CONCLUSION: Encephalopathy from low dose 5-Fluorouracil is not well documented in the literature. Fluid rehydration and supportive treatment is required. Signs and symptoms resolved completely with no residual effects on follow up.